China’s Foreign Policy Shift in South Asia vis-à-vis Belt and Road Initiative - Rashid, Sawaira; Ikram, Muhammad; Naeem, Muhammad Waqas (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
China’s foreign policy shift in South Asia has been largely driven by its Belt and Road Initiative (BRI), which seeks to enhance connectivity and economic cooperation across Asia and beyond. South Asia, with its strategic location and growing economic potential, has emerged as a key area of focus for China under the B RI. In this context, China has pursued a multi-pronged approach, which includes infrastructure development, economic cooperation, and strategic partnerships with key countries in the region. One of the key components of China’s foreign policy shift in South Asia has been its emphasis on infrastructure development. China has invested heavily in the construction of roads, railways, ports, and other infrastructure projects in the region, with the aim of improving connectivity and facilitating trade and commerce. These investments have been largely made through the BRI framework, which has provided China with a platform to promote its economic and strategic interests in the region. China has also sought to deepen economic cooperation with South Asian countries through the BRI. This has involved the signing of a number of bilateral and regional trade agreements, as well as the establishment of special economic zones and industrial parks. Through these initiatives, China has sought to increase its access to South Asian markets and promote the growth of its own economy. In addition to these economic initiatives, China has also sought to establish strategic partnerships with key countries in the region. This has involved strengthening its ties with countries such as Pakistan, Sri Lanka, and Bangladesh, which have strategic significance due to their location and their potential to provide China with access to key markets and resources. These partnerships have also involved cooperation in areas such as defense and security, with China seeking to establish a greater presence in the Indian Ocean region.